Becoming Taiwanese: Self-perception1 Of The New Taiwanese Immigrant Females - Chen, Mei ying (Penerbit Universiti Sains Malaysia (USM Press), 2010)
Southeast Asian and Chinese women have been marrying Taiwanese men since the 1980s. Nonetheless, cross-border marriages were not common until the 1990s, when the ″Go-South Policy″ was implemented. Unfortunately, these cross-border marriages have become commoditised. In addition, misperceptions broadcasted by the mass media have stigmatised these self-titled Taiwan new immigrant females (or TNIFs). This ethnographic research explores the self-perceptions of a particular group of TNIFs who have moved to Taiwan from urban regions in their homeland. Participant observation and in-depth interviews were employed to gather data, and these two sources of data were triangulated between one another. Research results indicate that many people came to Taiwan seeking a better life and not necessarily for economic reasons. However, their experiences in Taiwan have been largely unpleasant. Nevertheless, by working together with other TNIFs and Taiwanese people, they have come to call Taiwan their "home".